Cytokines in saliva, serum, and temporomandibular joint synovial fluid in children with juvenile idiopathic arthritis: An explorative cross-sectional study - Paula Frid; Josefine M. Halbig; Per Alstergren; Johanna Rykke Berstad; Lena Cetrelli; Astrid Jullumstrø Feuerherm; Berit Flatø; Annika Rosen; Karen Rosendahl; Marite Rygg; Veronika Rypdal; Nils-Thomas Songstad; et al. (Pediatric Rheumatology Online Journal)
Abstract Background Proinflammatory cytokines are central to disease mechanisms and important therapeutic targets in inflammatory chronic diseases. This exploratory study aimed to compare cytokine concentrations in saliva, serum, and temporomandibular joint (TMJ) synovial fluid in children with juvenile idiopathic arthritis (JIA) and controls. Methods In this cross-sectional study, we included consecutive children with JIA and TMJ arthritis, planned for a TMJ corticosteroid injection, and non-JIA controls from three different centers in Norway. Data on demographics, disease activity, presence of TMJ arthritis, and medication were obtained. Samples of unstimulated saliva, serum, and TMJ synovial fluid were collected. The amount of recovered synovial fluid in each sample, collected by the push-and-pull technique, was quantified with the hydroxocobalamin method. Cytokine levels were analyzed using Luminex xMAP technology. Results Fifteen patients with JIA and TMJ arthritis (JIA-TMJ) (median age 15.0 (interquartile range (IQR) 11.0–16.0) years) and 34 controls (median age 13.0 (IQR 9.8–15.0) years) were consecutively recruited. Samples of saliva (JIA-TMJ, n = 13, and controls, n = 28), serum (JIA-TMJ, n = 11, and controls, n = 16), and TMJ synovial fluid (JIA-TMJ, n = 8) were collected. In saliva from JIA-TMJ, we found significantly higher levels of the cytokines IL-1β, IL-4, IL-5, IL-9, IL-10, IL-12, IL-13, IL-17, Eotaxin, FGF basic, GM CSF, PDGF bb, TNF, and RANTES, while IP-10 was found in significantly lower concentration compared to controls. In serum, there were no significant differences in these cytokine concentrations between JIA-TMJ and controls. Three TMJ synovial samples fulfilled the strict sampling criteria and were included in the analysis. The level of detected cytokines in TMJ synovial samples was higher in JIA-TMJ compared to controls, as described in a previous Nordic study. Conclusions In this exploratory study, several proinflammatory cytokines were found in higher concentrations in saliva in JIA-TMJ compared to saliva from the controls. No differences were seen in serum between the groups. Some pro- and anti-inflammatory cytokines detected in JIA-TMJ synovial fluid were found in higher concentrations compared to TMJ synovial fluid from healthy adult reference data.